2017
DOI: 10.1097/ruq.0000000000000296
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Histogram Parameters on Elastography in Patients With Papillary Thyroid Microcarcinomas

Abstract: There were no significant associations between all histogram parameters on elastography and known poor prognostic factors such as extrathyroidal extension, lymph node metastasis, and high TNM stage in patients with PTMCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The quantitative elasticity index of PTC on preoperative SWE in combination with gray-scale US findings might be useful for predicting CLN metastasis. However, Yoon et al [77] reported that none of the histogram parameters on SE had significant associations with poor prognostic factors, including LN metastasis.…”
Section: Principles Of Us Elastography Techniques In the Thyroidmentioning
confidence: 99%
“…The quantitative elasticity index of PTC on preoperative SWE in combination with gray-scale US findings might be useful for predicting CLN metastasis. However, Yoon et al [77] reported that none of the histogram parameters on SE had significant associations with poor prognostic factors, including LN metastasis.…”
Section: Principles Of Us Elastography Techniques In the Thyroidmentioning
confidence: 99%
“…We totally recorded the value of 5 RTE images obtained from 5 different cardiac cycle for each patient, and the average of these 5 image parameters was used in analysis. Eleven quantitative parameters were totally obtained for each patient, including average relative strain value in the ROI (MEAN), standard deviation of relative strain value within the ROI (SD), area ratio of low-strain region (%AREA), complexity (COMP), kurtosis (KURT), skewness (SKEW), contrast (CONT), entropy (ENT), inverse difference moment (IDM), the angular second moment (ASM), and correlation (CORR) 19–21 . Depending on the differences in characterizing RTE image, the obtained 11 quantitative parameters for the image were divided into 3 types: parameters to describe color histogram (MEAN, SD, KURT, and SKEW), those for deformation (%AREA and COMP), and those for image texture (include CONT, ENT, IDM, CORR, and ASM).…”
Section: Methodsmentioning
confidence: 99%